Drug utilization of antibiotics in post-operative cesarean section inpatients in tertiary care hospital: a prospective observational study - B., Srinivasa; Kotinatot, Basavaraj C. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The aim of this study is to evaluate the pattern and rational use of antibiotics in post-operative caesarean section (CS) inpatients in tertiary care teaching hospital, BIMS Belagavi. Methods: This cross sectional prospective observational study was conducted from December 2019 to February 2020, prior permission from institutional ethics committee was taken. Detailed data of post-operative caesarean section (CS) inpatients including age, diagnosis, line of management, complications and any adverse effects if occurred during the study was collected and entered in a specially designed proforma and MS word excel and analyzed by descriptive statistics like percentage. Results: Total 100 post-operative caesarean section inpatients were involved in the study. Most common indication for C-section was cephalopelvic disproportion. Average no of antibiotics per prescription was 3.32. Most commonly prescribed antibiotic was cefotaxime (27.71%) followed by gentamycin (25.90%) and metronidazole (24.59%). Majority (90%) of patients who admitted for ≤3 days (66%) had received combination antibiotic i.e., cefotaxime, metronidazole and gentamycin. IV fluids (21.21%) and analgesics (13.13%) were most frequently prescribed concomitant drugs. Majority (97.8%) of patients received parenteral preparation. 306 antibiotics (92.17%) used were from national model list of essential medicines (NLEM) and 332 antibiotics (100%). used were by generic name. Polypharmacy was 7.92. Conclusions: Cefotaxime was the most frequently prescribed antibiotic. Most of the antibiotics prescribed was rationally from NLEM and were by generic name.